Lateral Access Minimally Invasive Spine Surgery - Wang, Michael Y.; Sama, Andrew A.; Uribe, Juan S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This well-illustrated textbook is the first comprehensive and authoritative source of information on minimally invasive lateral access spine surgery. It covers all aspects of the subject, including patient selection, approach and monitoring techniques, soft tissue management, application in a variety of pathologies, technical nuances, and the prevention and management of complications. In addition, current controversies in the field are discussed and the biomechanics of lateral spinal reconstruction, the physiologic benefits, and cost implications are explained. Over the past decade, the emergence of minimally invasive lateral access spine surgery has created a revolution in spine treatment. This trend began with the introduction of extreme lateral interbody fusion, a totally new spinal procedure. In recent years, the conversion of more than 15% of lumbar spinal fusion procedures to a lateral approach has been due to the unique advantages of this approach over conventional anterior or posterior surgery. All major purveyors of spinal products and implants have entered this market enthusiastically, and all major spinal societies now conduct annual cadaveric and didactic courses to teach the technique. As use of the lateral approach in spinal surgery has become more popular, so its diversity and complexity have increased. Nevertheless, coverage in the literature is typically limited to single chapters, and the spinal surgeon seeking to achieve optimal results must rely on chance discussions with colleagues at meetings to learn the latest information. Lateral Access Minimally Invasive Spine Surgery is designed to fill this vacuum. Written by world experts on the topic, it will be an excellent resource for both beginning and experienced surgeons.
Introduction: History and rationale for the minimally invasive lateral approach -- Biomechanics of lateral spinal reconstruction -- Physiologic benefits and the impact on the patient -- Costs and economic implications -- Workup and diagnostic injections -- Implants and lateral cages. Approach and localization: Patient selection -- Positioning and safety -- Intraoperative electrophysiologic monitoring -- Motor based monitoring -- Flouroscopic techniques -- Frameless navigation -- Techniques for avoiding psoas muscle and lumbosacral plexus injury. Soft tissue management: Single vs. dual incisions -- Retractor technology -- Transpsoas vs. Anterior To Psoas (ATP) -- Thoracic MIS retro pleural access -- Psoas muscle management. Pathologies: Degenerative disc disease -- Spondylolisthesis -- Scoliosis -- Sagittal deformities -- Neoplasia -- Trauma -- Infection -- Adjacent level disease & Proximal junctional kyphosis -- Technical Nuances: Lateral fixation -- Posterior fixation options -- ALL sectioning -- Surgery at the L5-S1 level -- Osteobiologics. Managing and preventing complications: Vascular -- Hollow viscus -- Hernia -- Pseudarthrosis. Controversies: Selective apical fusions -- Short segment vs. Long segment fusions -- Approaching a deformity from the concavity vs. convexity.
Keywords: Medicine; Neurosurgery; Orthopedics; Surgery; Medicine & Public Health; Neurosurgery; Surgical Orthopedics; Surgery